The sustainable development of mobility in the green transition: Renewable energy, local industrial chain, and battery recycling. (3rd October 2022) - D'Adamo, Idiano; Gastaldi, Massimo; Ozturk, Ilhan
Abstract: The transportation sector has a strong negative impact on the environment and therefore requires new sustainable development measures. This paper proposes a new indicator of sustainability in transport obtained through a multi‐criteria analysis based on Eurostat data and a panel of 10 academics. The results show a positive performance of Sweden in the period 2015–2019 and a small number of countries above the European average. Furthermore, a quantitative analysis based on these experts identifies the critical success factors associated with purchasing electric vehicles. The greatest importance is assigned to purchase cost, followed by battery autonomy. Our analysis proposes that electric vehicles are unable to achieve a sustainable transition unless three conditions are met: (i) use of renewable sources, (ii) local industrial development of the sector, and (iii) battery recycling. Therefore, Europe urgently needs to realize new industrial activities and avoid social unsustainability. The long‐term objective of a policy plan is to promote independence from external sources of energy, materials, and other resources.